2014
DOI: 10.1177/1060028014537611
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant Invasive Pulmonary Aspergillosis After a Near-Drowning Accident in an Immunocompetent Patient

Abstract: IFIs are uncommon in immunocompetent adults, but in the event of a near-drowning accident, environmental fungi can gain access to the human respiratory system and result in rapid, severe infection. Based on this case and the others described, it appears that near-drowning patients need an early initial evaluation for IFI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 18 publications
1
16
0
3
Order By: Relevance
“…Although samples from the site of the near-drowning episode were not sent for A. fumigatus culture, aspirated seawater and surrounding particulate material were presumed to be the source of his infection. We reviewed all cases of invasive pulmonary aspergillosis reported in the English literature, with one additional case in Japanese that was documented in another reference [9]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although samples from the site of the near-drowning episode were not sent for A. fumigatus culture, aspirated seawater and surrounding particulate material were presumed to be the source of his infection. We reviewed all cases of invasive pulmonary aspergillosis reported in the English literature, with one additional case in Japanese that was documented in another reference [9]. …”
Section: Discussionmentioning
confidence: 99%
“…Treatment varied considerably, although amphotericin B was used in the majority of cases. Unfortunately, invasive pulmonary aspergillosis after near-drowning is associated with significant morbidity, leading to prolonged hospitalization in every case and mortality in 50% of reported cases [49]. …”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary function tests showed that our patients had better forced expiratory volume in 1 second compared with European and North American reports. The underlying lung condition varied among patients given the diverse cause of PA, which can also develop in patients without underlying disease after intensive environmental exposure to Aspergillus spores [1,20,21]. Spectrum studies have also revealed a wide range of prevalence of tuberculosis or other underlying lung disease in PA patients, from 15.3% in Manchester, United Kingdom, to 93% in Korea [22][23][24].…”
Section: Commentmentioning
confidence: 98%
“…By contrast, immunocompetent subjects can have manifested features of invasive disease as soon as one day after massive environmental exposure to Aspergillus spores. 6 In the literature, a spectrum of disease is reported. Allergic broncho-pulmonary aspergillosis (ABPA) 7 and hypersensitivity pneumonitis to Aspergillus 2 and invasive pulmonary Aspergillus disease 4 can all occur following inhalation of high levels of spores.…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported sources for massive inhalation of Aspergillus spores include mouldy hay, 2 bark chippings 3 and rotten tree stumps, 4 mushroom pickers 5 and following near drowning 6 . With underlying immunosuppression, onset of disease is often insidious.…”
Section: Discussionmentioning
confidence: 99%